Genetic diversity of Neolamarckia cadamba using dominant DNA markers based on inter-simple sequence repeats (ISSRs) in Sarawak - Tiong, S.Y; Chew, S.F; Ho, W.S; Pang, S.L (Pelagia Research Library, 2014)
Neolamarckia cadamba or commonly known as kelampayan has been selected as one of the important plantation tree species in Malaysia. Thus, the molecular characterization of this indigenous tropical tree species is needed to maintain its high quality. Inter simple sequence repeats (ISSR) markers were used in this study to determine the genetic diversity and relatedness of N. cadamba in two planted forests and six natural forests in Sarawak. Three ISSR primers had generated atotal of 239 loci, of which 32.6% - 59.4% of the loci were polymorphic among236N. cadamba treesin eight populations. The mean Shannon’s diversity index (I)ranged from 0.1399 to 0.2354. The coefficient of population differentiation was low for planted forests (Gst = 0.0871) and natural forests (Gst = 0.2013`). Both UPGMA dendrogram and NJ-tree generated by ISSR markers had divided natural forests and planted forests into two distinct clusters. Natural forests were grouped in one cluster while planted forests were grouped in another cluster. This study shows that N. cadamba trees are closely related within its own population and its designated forest type. In future, several specific loci can be sequenced and developed into SCAR (sequence characterized amplification region) markers for tree improvement and conservation programme of N. cadamba.